A dynamic model of investment, total employment and producer price index for regional economies - Rodriguez, Tomas Miguel Pacolor (Animo Repository, 2015)
In this paper, we developed a dynamical model that portrays regional economic system focusing on the amount of Investment (X), number of Total Employment (Y ) and the value of Producer Price Index (Z). The model is built based on existing predator- prey biological models namely Chemostat model, Budworm model and Holling-Tanner predator-prey model. We nondimensionalized the model and linearized the system of equations at a xed point. We performed simulations at the calculated xed point (x y y ) where x > 0 and for cases where y is approximately equal to 1 and 1 2 . We have shown that for a system to be stable at the given xed point, Investment must approach zero. Otherwise, if the Investment grows without bound as time t ! 1, the sytem is unstable. In particular, Investment is bigger and PPI is smaller in the case of y 1 as compared to that of y 1 2 .